Analysis of the influence of the products’ nitrate pollution - Benderska (Dushchak), Olga; Bessarab, Alexander; Shutyuk, Vitaliy (My University, 2016)
We have analyzed contemporary research works, as well as literary sources containing information on the level of quality and safety of horticultural crops. The paper focuses mostly on the issue of food contamination by endogenous and exogenous substances. The key problem of the research is an excess of nitrates and their derivates which fruit and vegetables contain. According to the Ministry of Healthcare of Ukraine, 10% of plants contain more nitrates, than it is allowed by the maximum permitted level values. The actual statistical value of nitrates per capita in Ukraine amounts to approximately 260 mg/day, whereas the acceptable daily intake per day equals to 280 mg. On the basis of research analysis we have singled out the main reasons for ingestion of excessive amount of nitrates with food and defined the consequences of this process for consumers, having also advised a range of methods aimed at decreasing the amount of nitrates and their derivates. Ми проаналізували сучасні науково-дослідні роботи, а також літературні джерела, що містять інформацію про рівень якості та безпеки садівничих культур. Документ зосереджується в основному на питанні забруднення їжі ендогенними та екзогенними речовинами. Ключова проблема дослідження - надлишок нітратів та їх похідних, які містять фрукти та овочі. За даними Міністерства охорони здоров’я України, 10% рослин містять більше нітратів, ніж дозволено максимально дозволеними рівнями. Фактичне статистичне значення нітратів на душу населення в Україні становить приблизно 260 мг / добу, тоді як прийнятне щоденне споживання в день дорівнює 280 мг. На основі аналізу досліджень ми виділили основні причини поглинання надмірної кількості нітратів з їжею та визначили наслідки цього процесу для споживачів, також порадивши низку методів, спрямованих на зменшення кількості нітратів та їх похідних.
Keywords: нітрати; якість та безпека; збереження; забруднення; переробка; nitrates; quality and safety; conservation; contaminants; recycling; кафедра технології консервування